Features of Cost Advantages from Implementation of Energy-Saving Projects - Kvon, Gulnara M.; Prokopyev, Alexey I.; Shestak, Victor A.; Larionova, Anna A.; Shikh, Evgeniya V. (International Journal of Energy Economics and Policy, 2019)
The implementation of the tasks envisaged by the National Security Strategy provides for the creation and implementation of projects aimed at the formation of the appropriate infrastructure of the regions. The most important component of the regional infrastructure is the energy one, which ensures the solution of urgent problems of the population and enterprises of the regions in obtaining energy and heat supply services. The achievement of the abovementioned goal is provided by introduction of investment projects, the implementation of which makes it possible to obtain cost advantages by consumers of services. Analysis of these projects’ implementation programs over a long period of time confirms the significant cost advantages, the importance of which is determined by its social significance. The purpose of this paper is studying issues aimed at analyzing, assessment and shaping the cost benefits of the introduction of energy-efficient innovative technologies for heat-saving at enterprises of the public utilities sector. The study methods for this issue include the cost-benefit analysis, the cost efficiency assessment, tabular and graphical methods, which allow visualizing the structure of the economic effect and identifying its features. The paper presents the structure of the cost advantages gained by consumers that introduce innovative energy-saving technologies. The study revealed the features of the cost benefits formation, their structure, characteristic of these technologies. The paper draws a conclusion about the effectiveness of these projects, confirmed by the results of calculations, for consumers of services. Materials of the article are of practical value for professionals engaged in analysis and evaluation of energy/heat conservation projects, as well as for organizations that implement project outputs when comparing future benefits and costs as opposed to alternative technologies. Keywords: cost advantages; cost benefits; cost advantage assessment method; energy security; energy saving; heat saving; project costs and results. JEL Classifications: D24; Q43; M31 DOI: https://doi.org/10.32479/ijeep.7645